Inflation and the theory of money - Ball, R. J. (Chicago : Aldine Pub. Co., 1965)
This book seeks to provide a theoretical background to the analysis of inflation for third year specialists in economics and first year postgraduate students. The subject matter contains much that is highly controversial in professional circles, particularly as it has been orientated primarily toward the problem of inflation as it has manifested itself in the major industrialized countries since the Second World War.
Bibliographical footnotes.
osc 3/5/18
Loans
Keywords: Inflation (Finance)